PENGGUNAAN MEDIA JAMBOARD PADA MATA PELAJARAN IPA DI MASA PANDEMI DI MTSN 2 MEDAN - Epi Supriyani Siregar; Budi Alamasyah Siregar; Dewi Suma (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Based on the analysis of the data above about the most effective learning methods during covid-19 according to students when learning online, it shows that the perceptions of students and teachers about the most effective applications when learning online are the same, namely the most recommended use of Google Jamboard. The purpose of this activity is to see learning media that can support success based on the teaching and learning process as a form of effective teaching and learning activities in order to achieve the desired goals. The expected result after the implementation of this service is to increase the knowledge and understanding of students, teachers, and principals. This service activity is carried out as a form of caring and concern for the community to support and increase knowledge in the field of education, while the theme that we raise in this case is the socialization of how to use the Google Jamboard. After the completion of this activity in the future teachers, students and school principals during online learning the teacher will more easily provide science material to students IPA by using Google Jamboard.